A model for charge transfer in ultracold Rydberg ground-state atomic collisions. (16th May 2016) - Markson, Samuel; Sadeghpour, H R
Abstract: In excited molecules, the interaction between the covalent Rydberg and ion-pair channels forms a unique class of excited states, in which the infinite manifold of vibrational levels are the equivalent of atomic Rydberg states with a heavy electron mass. Production of the ion-pair states usually requires excitation through one or several interacting Rydberg states; these interacting channels lead to loss of flux, diminishing the rate of ion-pair production. Here, we develop an analytical, asymptotic charge-transfer model for the interaction between ultracold Rydberg molecular states, and employ this method to demonstrate the utility of off-resonant field control over the ion-pair formation, with near unity efficiency.